Automated Client-Side Monitoring for Web Applications - Choudhary, S.R.; Orso, A. (2009 International Conference on Software Testing, Verification, and Validation Workshops, 2009)
Web applications have become very popular today in a variety of domains. Given the varied nature of client-side environments and browser configurations, it is difficult to completely test or debug the client-side code of Web applications in-house. There are tools that facilitate functional testing on various browsers, but they cannot mimic all of the possible client-side environments. In modern Web browsers, the client-side code can interact with numerous Web services to get more data and even to update itself, which can in turn affect the behavior of the client in unforeseen ways. In these situations, monitoring the client-side code allows for gathering valuable runtime information about its behavior. In this paper, we propose a general technique for performing such monitoring. We also present a preliminary evaluation of the technique where we discuss its efficiency, effectiveness, and possible application scenarios.